Ama Ata Aidoo, Buchi Emecheta and Flora Nwapa: Feminist Critiques of PostColonial Africa - Mdluli , Yolanda (My University, 2022)
Beyond problematizing the marginal position of African women, African women have been authoring texts that contribute to socio-political debates about the ways in which African states were crafted to do little to nothing to placate the effects of colonialism after independence. Namely, Ama Ata Aidoo, Buchi Emecheta and Flora Nwapa are among the plethora of authors that have been doing this said project in their prose which is the main purpose behind why I chose to read and analyse a text by each of them for critiques of how Ghana and Nigeria transitioned from the colonial administration, respectively. I will look at how they not only contributed to these debates but also unpacked the dangers of being enticed by the imperial and masculinist form that many newly independent nations were taking. Their narratives will work to look at the usage of African literature in politics and not just as critically-acclaimed works of fiction.
A dissertation submitted in partial fulfilment of requirements of degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2022